Different Inhomogeneous Evolutionary Histories for Uranus and Neptune - Roberto Tejada Arevalo (The Astrophysical Journal Letters)
We present updated nonadiabatic and inhomogeneous evolution models for Uranus and Neptune, employing an interior composition of methane, ammonia, water, and rocks. Following the formation trends of the gas giants, Uranus and Neptune formation models are applied, where both planets begin with layers stable to convection. Both planets are subject to convective mixing throughout their evolution. Consistent with past work on this subject, the interior heat of Uranus evolution models is preserved by the stability of an outer composition gradient at lower initial entropy, where convective mixing is inhibited over evolutionary timescales. In contrast, if Neptune’s initial entropy is enough to convectively mix its envelope, it undergoes homogenization and adiabatic cooling of the outer 40% of its envelope. The subsequent release of internal energy during Neptune’s evolution, driven by the convective instability of its primordial outer compositional gradient, accounts for its higher luminosity relative to Uranus. This work proposes that the observed luminosity differences between Uranus and Neptune could be explained by the convective stability of their outer envelopes. The extensive convective mixing in Neptune can lead to a higher metallicity in its outer region compared to Uranus, a feature seen in atmospheric measurements and shown in past interior models of Neptune. Due to Neptune’s more pronounced cooling, our models predict favorable conditions for hydrogen–water immiscibility in its envelope.